2005
DOI: 10.4054/mpidr-wp-2005-016
|View full text |Cite
|
Sign up to set email alerts
|

Social capital related to fertility: theoretical foundations and empirical evidence from Bulgaria

Abstract: Working papers of the Max Planck Institute for Demographic Research receive only limited review. Views or opinions expressed in working papers are attributable to the authors and do not necessarily reflect those of the Institute.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 45 publications
5
30
0
2
Order By: Relevance
“…when individuals can rely on the help of relatives, friends, and colleagues, the effect of uncertainty is likely to be lower. Philipov (2003; see also Bühler and Philipov 2005) supported this finding for Bulgaria and Russia; Bühler and Fratczak (2007) for Poland;and Philipov, Spéder, and Billari (2006) for Bulgaria and Hungary.…”
Section: Effects Of Income On the Relationship Between Unemployment Amentioning
confidence: 69%
“…when individuals can rely on the help of relatives, friends, and colleagues, the effect of uncertainty is likely to be lower. Philipov (2003; see also Bühler and Philipov 2005) supported this finding for Bulgaria and Russia; Bühler and Fratczak (2007) for Poland;and Philipov, Spéder, and Billari (2006) for Bulgaria and Hungary.…”
Section: Effects Of Income On the Relationship Between Unemployment Amentioning
confidence: 69%
“…This finding is in line with the underlying assumption that grandparents, being close kin, not only will increase the likelihood that parents have another child by helping them out practically but also that they invest in subsequent children through other means, most notably communication of norms and expectations. Although we have not directly measured the communication between grandparents and parents, we know that kin can play an important role in fertility decisions (Bühler & Philipov, ; Rijken & Liefbroer, ). The potential usefulness of the kin influence hypothesis is further underscored by Sear and Coall's () study of grandparental involvement and fertility rates in 10 European countries.…”
Section: Discussionmentioning
confidence: 99%
“…Such an influence on decision making is not to be expected in the case of formal child care. The grandparents may have a particularly strong social influence on parents' fertility decisions (Bühler & Philipov, ). For instance, Waynforth () found that the mere physical presence of supportive parents rather than their financial or child care help encouraged reproduction in a 1970 British birth cohort sample.…”
Section: Introductionmentioning
confidence: 99%
“…This includes the perception of the expectations of significant others, such as those of the individual's partner, parents, and friends. Bühler and Philipov (2005) argued that individuals are embedded in social environments that affect their preferences. On the one hand, having access to certain resources can reduce the cost of having (further) children (Dommermuth et al 2011).…”
Section: Theoretical Backgroundmentioning
confidence: 99%